Jingle the brass - Newman, Patricia; Chesworth, Michael (New York : Farrar, Straus and Giroux, 2004)
On a train trip, an engineer teaches a boy the expressions used by railroad workers as he describes the different kinds of cars, freight, and people they see. Annotation. "Climb aboard and ride the point!" Step back in time to Ruby's rail-yard hash house and put on the nosebag with the boss hogger. He'll tell you he likes his eggs with headlights, but if you want scrambled, just order wreck on the main line. Follow him as he and his ashcat warm up engine number 417 at the roundhouse, give her a drink at the water tower, and then hitch her up to a jigger. Then jingle the brass and ride the point. Soon the rods will be flashing, because now you're railroading! Rhythmic text and busy, detail-filled pictures make learning train lingo loads of fun in this picture book that transports readers back to the heyday of steam locomotion.
A Junior Library Guild selection.
Keywords: Railroads -- Terminology -- Fiction; Railroad trains -- Fiction; Voyages and travels -- Fiction; Railroads -- Terminology -- Juvenile fiction; Railroad trains -- Juvenile fiction; Voyages and travels -- Juvenile fiction